Introduction And Development Of The Issue Of Gender Equality In Uzbekistan - Mokhidil, Davlatjonova (Jurnal Penelitian Ilmu Sosial dan Eksakta, 2024)
This literature review explores the intersection of gender equality and the evolving legal and social landscapes in Uzbekistan. As digital societies develop, the demand for gender-inclusive policies has increased, recognizing the unique contributions of women across various industries. Gender, defined as equal conditions for both sexes to exhibit personal qualities, is a focal point of this review. Historical milestones, such as the 1791 Declaration of Civility and the Rights of Woman and the 1948 Universal Declaration of Human Rights, underscore the long-standing struggle for gender equality. The analysis highlights contemporary efforts in Uzbekistan to ensure gender equality, including legislative advancements, educational opportunities, and the implementation of gender policies. The review examines the impact of these measures on the status of women in society and their participation in diverse professional fields. It concludes that the realization of gender equality is crucial for societal development and that Uzbekistan’s legal frameworks and initiatives play a vital role in promoting women’s active involvement in social and economic life.